Experiences and strategies of individuals with concomitant intellectual disabilities and cancer: a qualitative systematic literature review - Glasdam, Stinne; Cohen, Miri; Soffer, Michal; Fu, Cong (Frontiers in Cancer Control and Society, 2025)
BackgroundCancer care for individuals with intellectual disabilities (ID) is challenging, with evidence of disparities, late diagnoses, and overlooked experiences of the individuals in question.AimTo explore how individuals with concomitant ID and cancer experience the illness and navigate cancer care trajectories and everyday life from perspectives of themselves, their relatives and professionals.MethodA qualitative systematic literature review was conducted across the databases PubMed, EMBASE, CINAHL Complete, ERIC, SocINDEX, PsycInfo, and Scopus, supplemented by a final search in Google Scholar. All studies were screened and selected in Covidence according to predefined inclusion and exclusion criteria. The review included 16 publications, registered in PROSPERO (CRD420251042718) and followed the PRISMA guidelines. The quality of the included publications was assessed using the Critical Appraisal Skills Programme (CASP) checklist for qualitative research. Data extraction was followed by a descriptive summary and a qualitative thematic analysis, inspired by Braun and Clarke.ResultsThe studies, conducted in four countries, represented the voices of 22 individuals with ID and cancer and, in addition, perspectives of 11 relatives and 32 professionals. Data was synthesized in four themes: “Emotional responses to having cancer,” “Coping with cancer - life went on,” “Balancing the right to information and the limits of communication abilities,” and “Encountering death in various ways.” Individuals with ID responded to cancer and related challenges in diverse ways, yet they often demonstrated an ability to live in the moment as a coping strategy and strength in living and dying with cancer. They received information to varying degrees about their cancer diagnosis, treatment, and prognosis, while also having differing capacities to understand and process this information. Experiences of cancer in others contributed to their understanding of their own condition.ConclusionIndividuals with ID responded to cancer and its trajectory in varied ways. Many faced challenges in interactions with healthcare professionals, often due to communication barriers. Everyday routines and “living in the moment” served as important coping strategies. All 22 voices of individuals with ID represented in the studies came from the United Kingdom. Worldwide, future research should actively involve this population throughout the process.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251042718, PROSPERO: CRD420251042718.